Can the German Qualifications Framework contribute to the recognition of non-formal and informal learning? - Gutschow, Katrin [Verfasser]; Seidel, Sabine [Verfasser] (My University, 2011)
"As a consequence of introducing the European Qualifications Framework (EQF), according to the Recommendation of the European Parliament and Council of April 23, 2008, 'access to and participation in lifelong learning ... and the use of qualifications [should] be promoted and improved at national and Community level.' Furthermore, the EQF should build bridges between formal, non-formal and informal learning and contribute to the validation of learning outcomes. This article considers whether, and if so, how the EQF - and particularly the German Qualifications Framework for Lifelong Learning - can promote and strengthen the recognition of non-formal and informal learning. In addressing this line of inquiry, the authors make reference to two recent expertises on this subject." (Autorenreferat, BIBB-Doku)
Keywords: S 2.2.4.4 Anerkennung non-formaler Qualifikationen; Deutscher Qualifikationsrahmen; Lebenslanges Lernen; Informelles Lernen; Anerkennung